Influence Injecting Ovaprim With Different Doses Of Ovulation And Hatchery Siban Fish (Cyclocheilictys Apogon) - Sugistia D; Nuraini '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in February to April 2016 in the Laboratoryof Fish Hatchery and Breeding (PPI) Faculty of Fisheries and Marine SciencesUniversity of Riau. The purpose of this study was to determine the effect ovapriminjection of different doses of the ovulation and hatchery siban Fish. The methodused in this research is the method Experiment with direct observation of theobject being treated, by trying ovaprim different doses injected in siban fish _(Cyclocheilicthys Apogon). With completely randomized design (CRD) with afactor of four treatments and three replications. The treatments were P0 (0.9%sodium chloride injection of a dose of 0.2 ml / kg body weight of the mother), P1(ovaprim Injecting a dose of 0.3 ml / kg body weight of the mother), P2 (ovaprimInjecting a dose 0.5 ml / kg body weight of the mother), P3 (ovaprim Injecting adose of 0.7 ml / kg body weight of the mother).From the results of this study showed best treatment there in treatment P3with ovaprim dose of 0.7 ml / kg body weight, with an average latency time of7.07 hours, the number of eggs striping results as much as 365 grains / gramparent, the rate of conception by 77 , 16%, number of hatching at 77.75% and thenumber of survival by 77.98%. Water quality measurements during the study astemperature 28-300 C, pH 5-6 and 4.5 to 6.0 ppm dissolved oxygen.Keywords : siban Fish (Cyclocheilichthys apogon), Ovaprim, kelulushidupan